Redes metalo-orgânicas para carreamento e liberação de fármacos - Mori, Aline Sayuri [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The development and application of drug delivery systems have been contributing to improvements in patient life because increasing stability, better therapeutic efficacy and decreasing the adverse effects caused by the drugs. In order to overcome negative points of most of drug carriers described in the literature, news materials with greater drug encapsulation capacity and controlled release profile have been developed. Promising materials with these properties are the metal-organic frameworks (MOFs), which consist of organic and metallic blinders that form a highly porous and crystalline framework. Therefore, the aim of this study was to synthesize and characterize MOFs based on γ-cyclodextrin with several metals. Furthermore, to obtain a system with a differentiated release profile and a transdermal application, MOFs were incorporated into films of ureasyl-polyether class which presents interfacial compatibility, hydrogel behavior and have no toxicity. MOFs were synthetized based on a methodology described in the literature with some modifications, through a slow diffusion of methanol vapor. The X-ray diffractograms obtained had more pronounced and evident peaks in the MOFs obtained after 7 days of synthesis and confirmed the crystallinity of the material. The thermogravimetric data confirmed the formation of metal-organic framework and that the activation was effective eliminating solvent remnants in the material. The non-steroidal anti-inflammatory ibuprofen was incorporated in the MOFs, presenting high encapsulation efficiency, higher than 85%. The drug encapsulation efficiency and in vitro drug release of the MOFs were compared among themselves... (Complete abstract click electronic access below)

O desenvolvimento e aplicação de sistemas carreadores de liberação controlada de fármacos vêm contribuindo com a melhoria na qualidade de vida dos pacientes por proporcionar maior estabilidade, eficácia terapêutica e diminuição dos efeitos adversos ocasionado pelos medicamentos. Com o objetivo de superar alguns pontos negativos dos carreadores descritos na literatura, busca-se desenvolver novos materiais com maior capacidade de encapsulamento de fármaco e que apresente um perfil de liberação controlada. Dentre os materiais com estas propriedades estão as redes metalo-orgânicas (MOFs), constituídas por ligantes orgânicos e metálicos que formam uma rede altamente porosa e cristalina. Desta forma, o objetivo deste trabalho foi sintetizar e caracterizar as MOFs a base de γ- ciclodextrina e diferentes metais. Além disso, visando obter um sistema com perfil de liberação diferenciado e aplicação transdérmica, essas MOFs foram incorporadas em filmes da classe ureasil-polieter que apresentam elevada compatibilidade biointerfacial, comportamento hidrogel e não apresentam toxicidade. As MOFs foram sintetizadas baseando-se em uma metodologia descrita na literatura, com algumas modificações, através da difusão lenta de vapor de metanol. Os difratogramas de Raio X mostraram picos mais acentuados e evidentes no material com 7 dias de síntese e confirmaram a sua cristalinidade. A análise termogravimétrica confirmou a ativação efetiva eliminando resquícios de solvente. O fármaco ibuprofeno foi incorporado nas MOFs, apresentando alta eficiência de encapsulação, superior a 85%. As propriedades de encapsulação e perfil de liberação das MOFs foram comparadas... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ciclodextrinas; Medicamentos - Dosagem; Ions metalicos; Polímeros de coordenação; Antibacterianos; Anti-bacterial agents